Public administration pedagogy in India. (2nd July 2020) - Manoharan, Aroon P.; Viswanath, Shilpa; Sabharwal, Meghna
ABSTRACT: While the praxis of public administration in India is documented in the literature, its pedagogy, and the formal dissemination of its knowledge, is relatively unexamined. This study determines the status of public administration pedagogy in India through a review of the academic programs in public administration at accredited state, central, and deemed universities. After reviewing a sample of the syllabi of public administration programs, the academic context of the field, and the areas of key emphasis, this paper explores the conceptualization of public administration as an independent academic discipline in India. This study makes a significant contribution to global comparative public administration, and also contributes to developing the nascent literature on public administration pedagogy in present day India and South Asia.